2022
DOI: 10.1039/d1tb01815a
|View full text |Cite
|
Sign up to set email alerts
|

Less phagocytosis of viral vectors by tethering with CD47 ectodomain

Abstract: CD47 ectodomain tethered on the surface of lentiviral vectors endowing them with a phagocytosis-resistant feature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…HEK293T cell culture supernatant containing lentiviral particles obtained on the third day was concentrated according to a previous report. 54 Briefly, 10 mL of virus-containing supernatant was mixed with 10 mL of Polybrene solution (320 μg/mL) and incubated at 37 °C for 30 min. Then, the mixture was centrifuged at 10 000 g for 10 min at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…HEK293T cell culture supernatant containing lentiviral particles obtained on the third day was concentrated according to a previous report. 54 Briefly, 10 mL of virus-containing supernatant was mixed with 10 mL of Polybrene solution (320 μg/mL) and incubated at 37 °C for 30 min. Then, the mixture was centrifuged at 10 000 g for 10 min at 4 °C.…”
Section: Methodsmentioning
confidence: 99%
“…The collected supernatant that contains viruses were filtered through a 0.45 μm syringe filter. HEK293T cell culture supernatant containing lentiviral particles obtained on the third day was concentrated according to a previous report . Briefly, 10 mL of virus-containing supernatant was mixed with 10 mL of Polybrene solution (320 μg/mL) and incubated at 37 °C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, studies have demonstrated that LV vectors modified by the CD47ED fusion gene, incorporating extracellular domain-core of CD47 and streptavidin, can trigger phagocytosis of LV by antiphagocytic cells [ 147 ]. Notably, when BX795, an inhibitor of RIG-I, MDA5, and TBK1/IKKε complex downstream of TLR3, was employed to inhibit innate immune signals in cell lines, it resulted in significantly improved LV gene modification efficiency and enhanced LV transduction efficiency.…”
Section: Lentiviral Vector Therapymentioning
confidence: 99%